Tocilizumab, Remdesivir, Favipiravir and Dexamethasone Repurposed for COVID-19: The Risk Benefit Ratio at a Glance. - Mina Kelleni (2021)
This preprint has been peer reviewed, updated and published: https://link.springer.com/article/10.1007/s42399-021-00824-4 In this manuscript, we discuss the expectations versus the real word results of four repurposed COVID-19 drugs; tocilizumab, remdesivir, favipiravir and dexamethasone from a pharmacovigilant point of view. We recommend considering a personalized risk benefit ratio before a decision is made using any of these drugs. We suggest that though the results of phase III clinical trials have been less than expected; tocilizumab might have a potential to treat some critical cases of COVID-19. On the contrary, remdesivir, though its FDA approval, together with favipiravir are least likely to benefit COVID-19 patients. Finally, we recommend that the RECOVERY dexamethasone should only be further investigated and to be considered only for critical cases of hospitalized COVID-19 patients and we urge physicians in the developing countries to avoid and stop using it in mild-moderate COVID-19 cases.